The return of Marco Polo's world war, strategy, and American interests in the Twenty-first Century - Kaplan, Robert D. 1952- (Random House, 2018)
A bracing assessment of U.S. foreign policy and world disorder over the past two decades, anchored by a major new Pentagon-commissioned essay about changing power dynamics among China, Eurasia, and America...from the renowned geopolitical analyst and bestselling author of The Revenge of Geography and The Coming Anarchy. In the late thirteenth century, Marco Polo began a decades-long trek from Venice to China